Identification of a plasma microRNA profile in untreated pulmonary tuberculosis patients that is modulated by anti-mycobacterial therapy. Issue 4 (October 2018) - Barry, Simone E; Ellis, Magda; Yang, YuRong; Guan, Guangyu; Wang, Xiaolin; Britton, Warwick J; Saunders, Bernadette M
Highlights: Identified 87 miRs differentially regulated in TB patients versus healthy controls. 5 miRNA signature has biomarker potential to identify active TB patients. miRNA modified with successful anti-TB treatment, potential predictor of treatment success. Not all miRNA at baseline by therapy completion maybe ongoing remodelling in lungs. Summary: Objective: microRNA expression profiles are of interest as a biomarker of tuberculosis (TB). How anti-TB therapy effects miRNA profiles is unknown and was examined. Methods: We identified 87 plasma miRNAs that were significantly modified in an exploratory group of 19 Chinese pulmonary TB (PTB) patients compared to 14 healthy controls. We selected 10 of these miRNAs for analysis in a cohort of 100 PTB patients prior to, and at one, two and six months during treatment. Results: Five miRNAs were differentially expressed in PTB patients compared to controls at diagnosis; miRs −29a and −99b were up-regulated, whilst miRs −21, −146a and −652 were down-regulated. A combination of 5 miRNA distinguished TB from healthy controls with a sensitivity of 94%, a specificity of 88%, and an AUC of 0.976. Within one month of treatment, significant changes in miRs −29a, −99b, −26a and 146a levels occurred in successfully treated patients, although not all miRNAs returned to baseline by treatment completion. Conclusion: A 5-miRNA signature shows potential for development as a novel biomarker for TB disease with potential to predict response to treatment. The failure of all miRNA to return to baseline levels may reflect ongoing remodelling in the lung parenchyma that continues after completion of anti-TB therapy.